ПЕДАГОГИЧЕСКОЕ МАСТЕРСТВО ПРЕПОДАВАТЕЛЯ В УЧЕБНОМ ПРОЦЕССЕ НА ОСНОВЕ КОМПЛЕКСНОГО АНАЛИЗА ОБРАЗОВАТЕЛЬНЫХ ТЕХНОЛОГИЙ - Бабаева З. С. (International Journal of Innovative Technologies in Social Science, 2019)
The article raises the problem of assessing the level of pedagogical skills of the teacher. According to the author, each teacher can make to the existing educational technology of teaching students of a certain discipline their own scientifically based necessary corrections on the results achieved, which are specific changes that have occurred not only with the students themselves, but also in relations between students and the teacher.